Quête de caractérisation des profils pathologiques, itinéraires thérapeutiques et implications, sur les immigrants chez les CLOSM - Bahi, Boniface; Macleod, Andrea; Kamin, Mireille; Lamba, Moise; Vincent, Denis; Gaudet, Lyne; Dion, Michelle (University of Alberta, Campus Saint-Jean et Réseau Santé Alberta, 2024)
Ce projet de recherche piloté par le Réseau santé Alberta, en collaboration avec plusieurs directions régionales francophones de santé, s’est proposé d’étudier les enjeux de santé des immigrants francophones installés en Alberta, en Saskatchewan, au Yukon, dans les Territoires du Nord-Ouest, au Nunavut et en Terre-Neuve-et-Labrador, en référence aux déterminants sociaux de la santé et aux iniquités de santé perçues par ces francophones en situation minoritaire. Dans le but d’obtenir un aperçu général des enjeux rencontrés par ces francophones en situation minoritaire, cette étude a été réalisée afin de déceler un portrait global des défis de santé que rencontrent les francophones des régions ci-haut citées, à savoir les profils caractéristiques des pathologies émergentes de la population immigrante, les voies et moyens utilisés par ces immigrants pour pallier les difficultés liées et enfin, l’impact sur l’utilisation des services canadiens de santé des régions en question. En clair, chercher à identifier la nature de la pression de cette demande sanitaire immigrante. Entre autres, notre étude a un versant d’approche que nous indiquons comme épistémologies sanitaires comparées, relatives à des observations non participatives des phénomènes couramment vécus au sein des immigrants, qui arrivent au Canada dans un état de bonne santé, dans l’ensemble. Ils développent des maladies qu’ils n’avaient pas dans leurs conditions pré-migratoires, mais qui apparaissent avec le temps de vie au Canada. Les analyses documentaires, et notre sous-approche d’épistémologies sanitaires comparées liées aux études et des publications scientifiques antérieures portant sur les problèmes de santé des immigrants en général, et des francophones immigrants en situation minoritaire en particulier, aident à valider les données d’enquête. Celles-ci reposent sur les journaux de terrains professionnels des médecins de l’équipe de la recherche et de leurs réseaux de santé. Seules les études qui ont présenté une démarche scientifique et qui se sont appuyées sur des données empiriques, et celles se fondant sur une démonstration théorique, soit sur un modèle conceptuel ou sur une réflexion théorique, ont été retenues dans notre base documentaire analysée. Ces données s’ajoutent aux informations des 100 cas immigrants, et de celles des 25 professionnels des régions de l’étude. Les synthèses des informations permettent de soutenir que : - Les immigrants récemment arrivés au Canada ont un état de santé positif par rapports aux non immigrants canadiens - Cette santé se détériore au fur et à mesure que l’immigrant réside longtemps au Canada, à travers un mode de vie d’adhésion à de nouvelles habitudes de vie, en termes alimentaires et de relations sociales plus ou moins enviables, surtout, suivant les offres de possibilité ou non du milieu de vie canadien. - La santé mentale et les maladies chroniques font partie des états de morbidité (pathologies) que ces immigrants développent, comme expression de dégradation de leur santé. Une cause qui fédère la plupart des causes sectorielles, est le stress négatif qui surgit de l’écart entre les aspirations ou attentes pré-migratoires et ce que la réalité post-migratoire, la quotidienneté canadienne offre ou impose aux individus et aux groupes. - De ce qui précède, découlent des dysfonctionnements familiaux aux conséquences ou méfaits de tous ordres : liens conjugaux pathogéniques et conflictuels, liens filiaux (rapports parents-enfants) avec inversion d’autorité, etc… - Être immigrant et francophone limite l’accès aux services de santé pour des raisons linguistiques et d’offre rare de services spécialisés de santé correspondant à leur demande sanitaire, ce qui implique une prise en charge moindre de leurs problèmes de santé. C’est un processus cumulatif d’aggravation, voire de chronicisation de certains états pathologiques. - Les barrières linguistiques et la plupart des difficultés d’accès aux soins de santé qui en découlent constituent des principaux facteurs qui perpétuent les inégalités de santé perçues par les immigrants francophones en situation minoritaire par rapport à leurs homologues immigrants anglophones - Les francophones éprouvent des difficultés de santé liées, non seulement au fait de vivre dans un milieu linguistique minoritaire, mais, aussi, au fait d’être immigrant et de vivre dans un nouvel environnement avec une culture d’origine différente de celle de sa communauté d’accueil. - Beaucoup d’immigrants sont en quête de ressources humaines de santé homo-ethniques. En d’autres termes, ils vont à la recherche de thérapeutes de même origine ethnique. C’est ici que des églises évangéliques entrent en compte dans les itinéraires thérapeutiques. De part ces horizons sanitaires, des sphères pour la suite de la recherche, en termes de caractérisation de programmes d’intervention, se dessinent, en tenant compte des lacunes et besoins identifiés dans les services de soins de santé spécifiques aux immigrants. Des axes d’actions sont à envisager, en se fondant sur les principes de la Charte d’Ottawa (1986 et 2011) continuée par la Charte de Shanghai (2016). Les besoins sanitaires des immigrants sont en convergence avec ceux existants des populations francophones minoritaires qui les accueillent.

Insertion professionnelle dans le domaine de la santé des personnes immigrantes francophones vivant en situation minoritaire - Forest, Mariève; Goss Gilroy Inc (Ministère Immigration, Réfugiés et Citoyenneté Canada, 2020)

Gaps in knowledge and practices of malaria prevention in Francophone African immigrants in Metropolitan Edmonton - Hanna, Taylor A.; Ahmed, Ali; Vincent, Rémi; Coulibaly, Kongnon Sangué; Ahmed, Youssef; Petrick, Ryland; Vincent, Etienne; El Hafid, Mélanie; Hawkes, Michel T.; Ravi, Srilata; Gnidehou, Sedami (Malaria Journal, 2022)
Background Important knowledge gaps exist in the understanding of the management of the risks of imported malaria in Canada among Francophone immigrants from sub-Saharan Africa (FISSA). The aim of this cross-sectional study was to investigate the malaria related-knowledge, attitude and practices (KAP) of FISSA in Edmonton, where these immigrants are in an official minority language situation and the impact of language barriers on these factors. Methods A structured survey was used to examine the KAP of 382 FISSA in the Edmonton area from 2018 to 2019. Fisher’s Exact Test was applied to determine if there were associations between knowledge of malaria and different risk factors. Results Almost all FISSA (97%) had an accurate knowledge of fever as the key symptom of malaria. Interestingly, 60% of participants identified bed nets as a preventive method and only 19% of participants had accurate knowledge of malaria transmission. An accurate knowledge of symptoms was significantly associated with a high perceived risk of contracting malaria [odds ratio (OR) 4.33, 95% confidence interval (CI) 1.07–20.62]. Furthermore, even though 70% of FISSA had a high perceived risk of contracting malaria in endemic regions, only 52% of travellers had a pre-travel medical encounter. Importantly, language was not the predominant reason for not seeking pre-travel medical advice, although 84% of respondents chose French as their official language of preference when seeking medical advice. Having a French-speaking physician was correlated with satisfactory prevention knowledge (OR 1.96, 95% CI 1.16–3.35). With respect to health-seeking behaviour, 88% of respondents with a child < 5 years of age would seek medical care for fever in the child after travel to sub-Saharan Africa (SSA). Conclusion This study highlights that factors other than knowledge, risk assessment, and language might determine the lack of compliance with pre-travel medical encounters. It underscores the need for effective strategies to improve this adherence in minority settings.

La reconnaissance des diplômés internationaux francophones en santé : un potentiel pour les communautés francophones en situation minoritaire au Canada - Lafontant, Jean; Forgues, Éric; Belkhodja, Chedly; Sangwa-Lugoma, Ghislain; Meridji, Tayeb; Pietrantonio, Linda; Tremblay, André; Kayirangwa, Christine (Institut canadien de recherche sur les minorités linguistiques, 2006)

Experiences of French speaking immigrants and non-immigrants accessing health care services in a large Canadian city - Ngwakongnwi, Emmanuel; Hemmelgarn, Brenda. R.; Musto, Richard; Quan, Hude; King-Shier, Kathryn. M. (International Journal of Environmental Research and Public Health, 2012)
French speakers residing in predominantly English-speaking communities have been linked to difficulties accessing health care. This study examined health care access experiences of immigrants and non-immigrants who self-identify as Francophone or French speakers in a mainly English speaking province of Canada. We used semi-structured interviews to gather opinions of recent users of physician and hospital services (N = 26). Language barriers and difficulties finding family doctors were experienced by both French speaking immigrants and non-immigrants alike. This was exacerbated by a general preference for health services in French and less interest in using language interpreters during a medical consultation. Some participants experienced emotional distress, were discontent with care received, often delayed seeking care due to language barriers. Recent immigrants identified lack of insurance coverage for drugs, transportation difficulties and limited knowledge of the healthcare system as major detractors to achieving health. This study provided the groundwork for future research on health issues of official language minorities in Canada. Keywords: immigrants; French language; health care access; family doctor; qualitative descriptive; official language minorities

Portrait statistique sociosanitaire de la population immigrante de l’Ouest et du Nord - Santé en français (2023)
Le présent document pourra être utile aux parties prenantes de la santé des personnes immigrantes en contexte francophone minoritaire. Il vise à outiller ce public à mieux comprendre certaines dimensions du profil sociodémographique et sociosanitaire des personnes immigrantes en contexte francophone minoritaire. Pour ce faire des statistiques sont présentées sous forme de tableau et de graphique, puis interprétées de manière sommaire.

Access to healthcare services and confidence in healthcare professionals’ management of malaria: the views of Francophone sub-Saharan African Immigrants living in western Canada - Vincent, Rémi; Coulibaly, Kongnon Sangué; Ahmed, Ali; Ahmed, Youssef; Hanna, Taylor A.; Ravi, Srilata; Hawkes, Michael T.; Gnidehou, Sedami (BMC Public Health, 2023)
Abstract Background There is a paucity of knowledge about the healthcare attitudes and practices of French-speaking immigrants originating from Sub-Saharan Africa (FISSA) living in minority settings. The purpose of this study was to characterize FISSA healthcare experiences and confidence in the malaria-related knowledge of health professionals in Edmonton. Methods A structured survey was used to examine a cohort of 382 FISSA (48% female; 52% male) living in Edmonton. FISSA general healthcare attitudes, experiences and satisfaction with the Canadian healthcare system were studied. Healthcare Competency Perception (HCP) was characterized by using an index score. Statistical analyses were performed to evaluate the impact of healthcare experiences and other outcomes. Results Intriguingly, while only 42% of FISSA had a French-speaking family physician, 83% (197/238) of those who had received health care services in Alberta found that access to medical treatment was easy, and 77% (188/243) were satisfied with received care. Although 70% (171/243) of FISSA did not receive services in French, 82% (199/243) surprisingly reported having good levels of comprehension during their visits. Satisfaction with care was associated with having a family physician (p = 0.018) and having health insurance (p= 0.041). Nevertheless, confidence in the healthcare system’s ability to treat malaria effectively was significantly lower, with only 39% (148/382) receiving a positive score on the HCP index. Conclusion This study provides an important insight into FISSA experience with and perception of the Alberta’s healthcare system.

Construction of Francophone families’ health literacy in a linguistic minority situation - Zanchetta, Margareth. Santos; Kaszap, Margot; Mohamed, Mohamed; Racine, Louise; Maheu, Christine; Masny, Diana; Cèsar, Ines; Maltais, Claire; Sangwa-Lugoma, G.; Lussier, Nancy; Kinslikh, Diana (Alterstice, 2012)
With the increase in international mobility, healthcare systems should no longer be ignoring language barriers. In addition to the benefit of reducing long‐term costs, immigrant‐friendly organizations should be concerned with mitigating the way language barriers increase individuals’ social vulnerabilities and inequities in health care and health status. This paper reports the findings of a qualitative, exploratory study of the health literacy of 28 Francophone families living in a linguistic‐minority situation in Canada. Analysis of interviews revealed that participants’ social vulnerability, mainly due to their limited social and informational networks, influenced the construction of family health literacy. Disparities in access to healthcare services could be decreased by having health professionals’ work in alliance with Francophone community groups and by hiring bilingual health professionals. Linguistic isolation and lack of knowledge about local cultural organizations among Francophone immigrants were two important findings of this study.